Prediction of CD3 T cells and CD8 T cells expression levels in non-small cell lung cancer based on radiomic features of CT images - Chen, Lujiao; Chen, Lulin; Ni, Hongxia; Shen, Liyijing; Wei, Jianguo; Xia, Yang; Yang, Jianfeng; Yang, Minxia; Zhao, Zhenhua (Frontiers in Oncology, 2023)
In this work, radiomics characteristics based on CT scans were used to build a model for preoperative evaluation of CD3 and CD8 T cells expression levels in patients with non-small cell lung cancer (NSCLC).